Caractérisation De La Pêche Au Lac Kivu - Akonkwa Balagizi; Ahouansou Montcho Simon; Nshombo Muderhwa; Lalèyè Philippe (European Scientific Journal, ESJ, 2017)
This study was focused on the description of fishing gears on Lake Kivu. Data were collected from March 2012 to February 2014 in Goma, Bukavu, and Kibuye fishing stations. The study findings indicate that gill nets, beach seine, lift net, trammel net composed of two panels of small and larger meshes (mosquito net attached to lift net parts), mosquito net, longline, single line, pots, and cast net were identified as fishing gears used on Lake Kivu. Longline was more selective (2 species) in terms of species selection. The lift net presented the best catch (19.4 ± 11 kg), while the trammel net showed the highest CPUE (7.9 ± 6.1 kg/h). The large dimensions of gears and the long netting duration characterized gillnets (1023.2 ± 620.1 m2 ) and longline (10.3 ± 4.6 hours) respectively. Cast-nets (20mm) showed the largest mesh size, while mosquito nets (1 ± 0.3 mm) were the smallest.